READING WORKS, INTERPRETING WORLDS: A POSTMODERN-LITERARY EXPLORATION IN FREDERIC JAMESON'S HORIZON - Nurhidayah, Sri; Setiawan, Rahmat (Balai Bahasa Provinsi Jawa Timur, 2022)
This conceptual article aims to explore literary works through the perspective of Fredric Jameson. Literary works have legitimacy as a critical space for real problems, however, many of them also expose the author’s ideological side or reality. This is the political unconsciousness. This research approach is grounded theory because this exploration moves from the empirical realm to the theory-based realm in analyzing data. The data are in the form of quotation statements taken from relevant reference books, articles or journals. The data collection technique is documentation because this research is a type of library research. The analysis technique is thematic analysis. From the exploration results, it can be seen that Jameson sees a text as a symbolic act, resistant but reproducible to the dominant ideology. This is the condition of reification, in which the subject (writer and/character) is drowning to a process of totalization towards unconsciousness which is inherent in ideological power. This is the political unconscious which leads us to the unmasking of cultural artifacts (literary texts) as interpreted social symbolic actions